Hubungan Tumpatan Glass Ionomer Cement dan Pertumbuhan Streptococcus Mutans di Dalam Saliva - Lelly Andayasari; Magdarina Destri Agtini (Faculty of Dentistry, Universitas Indonesia, 2015)
The study was a quasi experimental one, supported by microbiological data. The respondents had been purposively chosen from three Bekasi elementary schools in 2002, with 72 children as treatment group and 72 children as control group. Data collected included oral and laboratory examinations. Dental health status of permanent dentition was determined using the DMF-T index. The data was collected at the start and 120 days after intervention. Data analysis was by paired t-test for before and after treatment, and by independent t-test for comparating treatment and control. For the average the means 2 samples t-test difference was used, and for the average difference between the same groups the mean one sample t-test was applied. For the nominal scale proportion difference the likelihood ratio test was applied, and for the ordinal scal the nonparametric one-way Anova was used. Simple regression test was used to determine the relation between dependent and independent variables. The results of the study show decrease of S. mutans colonies in saliva after treatment (p= 0,001) and decreasing DMF-T score for treatment group. In control group, there is no decrease in  S. mutans colonies, but increasing DMF-T score was found. The conclusion was that glass ionomer cement fillings can inhibit S. mutans growth in saliva.